Battery separator and preparation method thereof, battery and electrical equipment

By using functional layers of polyphthalylphenylenediamine, binder and plasticizer in the battery separator, the problem of insufficient performance in high temperature and mechanical strength of the battery separator is solved, and higher safety performance and cycling performance are achieved.

CN119764753APending Publication Date: 2025-04-04CHONGQING FUDI BATTERY RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410544485.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing battery separators lack performance in high temperature and mechanical strength, and the strong water absorption of polyphthalylphenylenediamine causes the membrane to lose water in a low dew point environment, resulting in curling and sagging, affecting flatness and safety performance.

Method used

Using a functional layer including polyphthalylphenylenediamine, binder and plasticizer, the mechanical properties and high temperature resistance are improved through the hydrogen bond cross-linking network of polyphthalylphenylenediamine, and the intermolecular entanglement is alleviated through the plasticizer to prevent the curling and sagging caused by water loss.

Benefits of technology

It significantly improves the high temperature resistance, mechanical strength and flatness of the battery separator, reduces the lateral and longitudinal shrinkage rates at high temperatures, and improves the safety and circulation performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764753A_ABST
    Figure CN119764753A_ABST
Patent Text Reader

Abstract

The present application provides a battery separator and a preparation method thereof, a battery and an electrical device. The functional layer in the battery separator can effectively improve the high temperature resistance and mechanical strength of the battery separator, which is beneficial to improving the safety performance of the battery; in addition, the functional layer itself has adhesiveness, and curling and sagging are not easy to occur during the battery manufacturing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery separators, and in particular to battery separators and preparation methods thereof, batteries and electrical equipment. Background Art

[0002] In order to improve the high temperature resistance and mechanical strength of the battery separator, the industry has tried to set a polyphenylene phthalate layer on the surface of the base film (for example, a polyolefin separator). However, polyphenylene phthalate does not have adhesion to the electrode, and generally, an adhesive layer needs to be set on the surface of the side of the base film away from the polyphenylene phthalate layer to fix it to the electrode, resulting in a significant increase in the thickness of the battery separator, which is not conducive to the application of the battery separator. In addition, because polyphenylene phthalate is only set on one side of the base film at this time, the performance improvement of the battery separator is limited. In addition, especially for stacked batteries, the flatness requirements of the battery separator are relatively high, and polyphenylene phthalate itself has strong water absorption, which will cause the aramid layer to lose water quickly in a low dew point environment during the battery manufacturing process, causing the separator to curl and droop, resulting in a decrease in the flatness of the battery separator, which is not conducive to the application of the battery separator. Summary of the invention

[0003] In view of this, the embodiments of the present application provide a battery separator and a preparation method thereof, a battery and an electrical device. The functional layer in the battery separator can effectively improve the high temperature resistance and mechanical strength of the battery separator, which is beneficial to improving the safety performance of the battery; in addition, the functional layer itself has adhesiveness, and curling and sagging are not easy to occur during the battery manufacturing process.

[0004] A first aspect of an embodiment of the present application provides a battery separator, comprising a base film and a functional layer disposed on at least one surface of the base film, wherein the functional layer comprises polyphenylene phthalate, a binder and a plasticizer.

[0005] The molecular chain of polyphenylenediamine is relatively rigid, and a hydrogen bond cross-linking network can be formed between polyphenylenediamine molecules, so the functional layer is relatively rigid, which can improve the mechanical properties of the battery separator; at the same time, polyphenylenediamine has good high temperature resistance, which can effectively increase the membrane breaking temperature of the battery separator, reduce the risk of short circuit or even combustion and explosion caused by failure of the battery separator in the case of thermal runaway, and improve the safety performance of the battery. At the same time, plasticizers can effectively alleviate the molecular entanglement of polyphenylenediamine, alleviate the curling and drooping of the battery separator caused by the molecular chain movement caused by water loss in the low dew point environment of polyphenylenediamine in the subsequent process, improve the flatness of the battery separator, and be more conducive to its application in the battery; further, it can also improve the thermal shrinkage resistance of the battery separator, specifically reduce the lateral shrinkage rate and longitudinal shrinkage rate of the battery separator at high temperature, thereby further improving the safety performance of the battery.

[0006] In addition, the binder makes the functional layer itself adhesive, which is beneficial to improve the energy density of the battery. Furthermore, based on the superior hygroscopic performance of poly(p-phenylene terephthalamide), the battery separator provided in the embodiment of the present application has a stronger electrolyte retention capacity, which is beneficial to improve the cycle performance of the final battery. Therefore, the battery separator provided in the embodiment of the present application can be used to provide a battery with both high safety performance and superior cycle performance.

[0007] The second aspect of the embodiment of the present application provides a method for preparing a battery separator, which can be used to prepare the battery separator provided in the first aspect of the embodiment of the present application, and the preparation method comprises:

[0008] S01, mixing polyphenylene phthalamide, a binder and a plasticizer to obtain a functional layer slurry;

[0009] S02. Applying a functional layer slurry on at least one side of the base film to obtain a prefabricated film with a cast film layer, causing the cast film layer to undergo a phase transformation to form a functional layer, thereby obtaining a battery separator.

[0010] The preparation method has simple process, strong controllability, high production efficiency and is suitable for large-scale industrial production.

[0011] The third aspect of the embodiment of the present application provides a battery, comprising a positive electrode, a negative electrode and the battery separator provided in the first aspect of the embodiment of the present application, wherein the battery separator is located between the positive electrode and the negative electrode. Due to the use of the battery separator provided in the embodiment of the present application, the above battery can achieve higher safety performance and better cycle performance.

[0012] The fourth aspect of the embodiment of the present application provides an electric device, including the battery provided by the third aspect of the embodiment of the present application. Since the battery provided by the embodiment of the present application is used to power the electric device, the electric device has strong market competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1A A schematic structural diagram of a cross section of a battery separator is provided for one embodiment of the present application;

[0014] Figure 1B A schematic structural diagram of a cross section of a battery separator is provided for one embodiment of the present application;

[0015] Figure 2A This is a photo of the battery separator provided in Example 3 of the present application after being placed in a -20°C dew point environment for 103 hours;

[0016] Figure 2B This is a photo of the battery separator provided in Example 5 of the present application after being placed in a -20°C dew point environment for 103 hours;

[0017] Figure 3A scanning electron microscope (SEM) photograph of the surface of the functional layer of the battery separator provided in Example 3 of the present application facing away from the base film;

[0018] Figure 4 This is a photograph of the battery separator provided in Comparative Example 1 after being placed in a -20°C dew point environment for 103 hours. DETAILED DESCRIPTION

[0019] In the related art, in order to improve the problems of poor high temperature resistance and low puncture resistance of polyolefin separators, a polyphenylene phthalate layer is selected to be set on the surface of the base film. However, since polyphenylene phthalate has no adhesion to the electrode, it is necessary to set an adhesive layer on the surface of the side of the base film away from the polyphenylene phthalate layer. At this time, if the same enhancement effect is to be achieved, the thickness of the battery separator needs to be significantly increased, which affects the energy density of the battery, and the production process is relatively cumbersome; and, if polyphenylene phthalate is only set on one side of the base film, the performance improvement of the battery separator is limited. Because polyphenylene phthalate has strong water absorption, in the low dew point environment (for example, -20°C dew point environment) that needs to be experienced in the subsequent battery manufacturing process, the polyphenylene phthalate layer is prone to rapid water loss, resulting in curling and sagging of the separator, and the flatness of the separator is reduced, which affects its application in batteries, especially its application in laminated batteries.

[0020] In order to solve the above technical problems, the present application embodiment provides a battery separator, see Figure 1A The battery separator 1 includes a base film 10 and a functional layer 20 disposed on at least one side of the base film 10, and the functional layer 20 includes polyphenylene phthalate, a binder, and a plasticizer. In the embodiment of the present application, infrared spectroscopy or X-ray photoelectron spectroscopy (XPS) can be used to characterize the presence of polyphenylene phthalate, a binder, and a plasticizer.

[0021] The molecular chain of polyphenylenediamine is relatively rigid, and a hydrogen bond cross-linking network can be formed between polyphenylenediamine molecules, so the functional layer is relatively rigid, which can improve the mechanical properties of the battery separator, for example, puncture resistance, which can reduce the risk of battery short circuit; at the same time, polyphenylenediamine has good high temperature resistance, which can effectively increase the rupture temperature of the battery separator, reduce the risk of short circuit or even combustion and explosion caused by failure of the battery separator in the case of thermal runaway, and improve the safety performance of the battery. At the same time, plasticizers can effectively alleviate the molecular entanglement of polyphenylenediamine, alleviate the phenomenon of curling and drooping of the battery separator caused by the molecular chain movement caused by water loss in the low dew point environment of polyphenylenediamine in the subsequent process, improve the flatness of the battery separator, and be more conducive to its application in the battery; further, it can also improve the thermal shrinkage resistance of the battery separator, specifically reduce the lateral shrinkage rate and longitudinal shrinkage rate of the battery separator at high temperature, thereby further improving the safety performance of the battery. In some embodiments of the present application, the transverse shrinkage of the battery separator at 130°C is ≤3.5%, and the longitudinal shrinkage is ≤4.5%. For example, the transverse shrinkage of the battery separator at 130°C is 1.2%-3.2%, and the longitudinal shrinkage is 1.9%-4.3%. In the embodiment of the present application, the test of the transverse shrinkage and longitudinal shrinkage of the battery separator includes: cutting the battery separator into samples of a certain size, using an imager to measure the length in the transverse (TD) and longitudinal (MD) directions, sandwiching each sample in an A4 paper and placing it in an oven, baking at 130°C for 1h, taking out the length in the TD and MD directions after baking for testing; transverse shrinkage = (TD size before baking - TD size after baking) / TD size before baking × 100%, longitudinal shrinkage = (MD size before baking - MD size after baking) / MD size before baking × 100%.

[0022] In addition, the adhesive makes the functional layer itself adhesive, so there is no need to set an additional adhesive layer on the base film; in the embodiment of the present application, the peeling force between the battery separator and the electrode is >1N / m. In this way, when other parameters are equal (the base film is the same, the total thickness of the battery separator is equal), the battery separator of the embodiment of the present application has better high temperature resistance and mechanical strength; in other words, for the same base film, when the equivalent high temperature resistance and mechanical strength are achieved, the battery separator provided by the embodiment of the present application has a smaller thickness, which can improve the energy density of the battery. Because there is no need to set a separate adhesive layer on the other side surface of the base film, the above-mentioned functional layer can be set on both sides of the base film. It can be understood that those skilled in the art can choose to set the functional layer on one side of the base film according to actual production needs, or can set the functional layer on both sides of the base film (such as Figure 1BAs shown). In some embodiments of the present application, the functional layer is provided on both sides of the opposite surfaces of the base film. In this way, it is more conducive to improving the mechanical properties and high temperature resistance of the battery separator. In some embodiments of the present application, the puncture strength increment of the battery separator relative to the base film is 0.5kgf-2kgf, for example, 0.5kgf, 0.8kgf, 1.0kgf, 1.2kgf, 1.5kgf, 1.8kgf, etc. In an embodiment of the present application, a puncture strength tester can be used to test the puncture strength A1 of the battery separator. In an embodiment of the present application, the functional layer is peeled off from the surface of the base film, and then the puncture strength tester is used to test the puncture strength A2 of the base film. The puncture strength increment of the battery separator relative to the base film is equal to A1-A2. Specifically, the needle puncture diameter of the puncture strength tester is 1mm, and the opening diameter of the puncture fixture is 10mm; samples are cut at a certain interval along the width direction (TD) of the battery separator, and the samples are placed in the fixture to ensure that the surface of the sample is flat and not twisted. The puncture is performed at a speed of 50mm / min, and the puncture force value is recorded after the sample is punctured.

[0023] Furthermore, based on the superior hygroscopic properties of poly(p-phenylene terephthalamide), the battery separator provided in the embodiment of the present application has a stronger electrolyte retention capacity, which is beneficial to improving the cycle performance of the final battery, for example, extending the cycle life of the battery, etc. Therefore, the battery separator provided in the embodiment of the present application can be used to provide a battery with both higher safety performance and better cycle performance.

[0024] In the embodiment of the present application, polyphenylene phthalamide includes poly(p-phenylene terephthalamide) and / or poly(m-phenylene isophthalamide). Poly(p-phenylene terephthalamide) has relatively higher strength and modulus and good high temperature resistance, while poly(m-phenylene isophthalamide) has excellent high temperature resistance and better flame retardancy and mechanical properties.

[0025] In some embodiments of the present application, the functional layer has a three-dimensional network structure formed by overlapping fibers, and the granular binder is dispersed in the three-dimensional network structure; the material of the fiber includes polyphenylene phthalate and a plasticizer. That is, the functional layer includes a three-dimensional network structure formed by overlapping composite fibers composed of polyphenylene phthalate and a plasticizer, and the granular binder is dispersed in the above three-dimensional network structure. The composite fiber composed of polyphenylene phthalate and a plasticizer has good rigidity, which can ensure that the mechanical properties of the battery separator are good, and the above three-dimensional network structure has a high porosity, so it is beneficial to ensure the liquid retention performance of the battery separator, and provide sufficient channels for the transmission of active ions (for example, lithium ions) during the battery charge and discharge cycle, which is beneficial to the battery cycle performance. At this time, SEM can be used to characterize the presence of the binder.

[0026] In the embodiments of the present application, the thickness of the functional layer is not limited, and those skilled in the art can select it according to actual production needs. In some embodiments of the present application, the thickness of the functional layer is 1 μm-4 μm, specifically 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, etc. In this way, the comprehensive performance of the battery separator is better.

[0027] In order to reduce the risk of agglomeration of binder particles and optimize the adhesion of the functional layer, in some embodiments of the present application, the primary particle size of the granular binder is controlled within the range of 50nm-200nm. Even if aggregation occurs, the particle size of the secondary particles aggregated from the primary particles is 0.5μm-5μm. In the embodiments of the present application, the particle size of the granular binder can be observed under a scanning electron microscope. Specifically, the primary particle size of the granular binder can be, but is not limited to, 50nm, 80nm, 100nm, 120nm, 150nm, 180nm, 200nm.

[0028] In some embodiments of the present application, the binder includes one or more of polyvinylidene fluoride, polymethyl methacrylate, polyamide and polyacrylic acid. The above binder can effectively improve the bonding performance of the functional layer and has good compatibility with other substances in the battery.

[0029] In some embodiments of the present application, the mass ratio of plasticizer to polyphenylene phthalate is 1:(8-300). In this way, the flatness and heat shrinkage resistance of the battery separator in a low dew point environment can be effectively improved, while the battery separator also has a high puncture resistance, fully ensuring the high safety performance of the final battery. Specifically, the mass ratio of plasticizer to polyphenylene phthalate can be, but is not limited to, 1:8, 1:10, 1:20, 1:30, 1:40, 1:50, 1:80, 1:100, 1:120, 1:150, 1:180, 1:200, 1:220, 1:250, 1:300. In the embodiment of the present application, the functional layer can be peeled off from the base film, and then the mass ratio of plasticizer to polyphenylene phthalate (TGA) can be tested.

[0030] In some embodiments of the present application, the mass ratio of the binder to polyphenylene phthalate satisfies 1:(8-30). The higher the mass ratio of polyphenylene phthalate, the more conducive it is to improving the film breaking temperature of the battery separator. However, controlling the mass ratio of the two within the above range can make the battery separator have both strong bonding performance and electrolyte retention capacity, and will not significantly affect the film breaking temperature of the battery separator, so the final safety performance and cycle performance of the battery are better. Specifically, the mass ratio of the binder to polyphenylene phthalate can be, but is not limited to, 1:8, 1:10, 1:12, 1:15, 1:18, 1:20, 1:22, 1:25, 1:28, 1:30. In the embodiment of the present application, the functional layer can be peeled off from the base film, and then the mass ratio of the binder to polyphenylene phthalate (TGA) can be tested by thermogravimetric analysis (TGA).

[0031] In some embodiments of the present application, the mass ratio of polyphenylene phthalate, binder and plasticizer satisfies (8-30): 1: (0.1-1). In this way, the comprehensive performance of the battery separator is better, which is specifically manifested in that its high temperature resistance, peel strength with the pole piece and electrolyte retention capacity are significantly improved, and when finally assembled into the battery, the safety performance and cycle performance of the battery are better. Preferably, the mass ratio of polyphenylene phthalate, binder and plasticizer satisfies (12-18): 1: (0.3-0.5). Specifically, the mass ratio of polyphenylene phthalate, binder and plasticizer can be but is not limited to (8-30):1:(0.1-0.2), (8-30):1:(0.1-0.5), (8-30):1:(0.1-0.8), (10-15):1:(0.2-0.5), (10-18):1:(0.2-0.5), (12-18):1:(0.2-0.5), (12-18):1:(0.3-0.5), (12-18):1:(0.4-0.8), (12-25):1:(0.5-0.9), etc.

[0032] In some embodiments of the present application, the plasticizer includes but is not limited to triethyl phosphate, tributyl phosphate, tricresyl phosphate, dioctyl adipate, diisodecyl adipate, dioctyl azelate, dioctyl sebacate, dioctyl phthalate, dibutyl phthalate, dimethyl phthalate, diethyl phthalate, epoxy fatty acid butyl ester, dipentaerythritol ester and one or more of ethylene glycol ester. The above plasticizer can effectively alleviate the intermolecular entanglement of polyphenylene phthalide, and has good compatibility with other substances in the battery system (for example, electrolyte, etc.), which can avoid unnecessary side reactions during the charge and discharge cycle of the battery.

[0033] It is understandable that the base film also needs to be infiltrated by the electrolyte, so it has a certain porosity. In some embodiments of the present application, the porosity of the base film is 30%-55%. Specifically, the porosity of the base film can be but is not limited to 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 55%, etc.

[0034] In some embodiments of the present application, the material of the base film can be the material of the base film commonly used in the field. Specifically, the material of the base film includes but is not limited to one or more of polyolefin, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyimide, polyester and polyurethane. It is understandable that the base film can be selected from the base film of the battery separator commonly used in the field, for example, polyethylene microporous film, polypropylene microporous film, polypropylene / polyethylene / polypropylene three-layer composite microporous film, polyvinylidene fluoride microporous film, polyvinylidene fluoride-hexafluoropropylene microporous film, polyimide microporous film, polyethylene non-woven fabric, polypropylene non-woven fabric, polyester non-woven fabric, polyimide non-woven fabric, spandex non-woven fabric, etc., and the present application does not limit this. The embodiment of the present application also does not limit the thickness of the base film.

[0035] In some embodiments of the present application, the liquid absorption rate increment of the battery separator relative to the base film is 50%-100%. Specifically, the liquid absorption rate increment of the battery separator relative to the base film can be, but is not limited to, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, etc. In the embodiments of the present application, the test of the liquid absorption rate of the battery separator includes: weighing the battery separator after drying, soaking the battery separator in the electrolyte for 2 hours, taking out and draining until no liquid drops, testing the mass of the battery separator after liquid absorption, and the liquid absorption rate of the battery separator B1 = (battery separator mass after liquid absorption - battery separator mass before liquid absorption) / battery separator weight before liquid absorption × 100%. In the embodiments of the present application, the base film is separated from the functional layer, and the liquid absorption rate B2 of the base film is tested according to the above test method. The liquid absorption rate increment of the battery separator relative to the base film is equal to B1-B2.

[0036] In some embodiments of the present application, the air permeability increment of the battery separator relative to the base membrane is ≤50s / 100mL. In the embodiment of the present application, an air permeability tester can be used to test the air permeability C2 of the battery separator C1 and the base membrane. Specifically, the battery separator is laid flat on the measuring position of the air permeability tester to test its permeability value; 10 points are selected along the TD direction of each battery separator for testing and the average value is taken. In the embodiment of the present application, the base membrane is separated from the functional layer, and the air permeability C2 of the base membrane is tested according to the above-mentioned test method. The air permeability increment of the battery separator relative to the base membrane is equal to C1-C2, and the units of C1 and C2 are both s / 100mL.

[0037] The present application also provides a method for preparing a battery separator, which can be used to prepare the aforementioned battery separator. The method comprises:

[0038] S01, mixing polyphenylene phthalamide, a binder and a plasticizer to obtain a functional layer slurry;

[0039] S02. Applying a functional layer slurry on at least one side of the base film to obtain a prefabricated film with a cast film layer, causing the cast film layer to undergo a phase transformation to form a functional layer, thereby obtaining a battery separator.

[0040] The preparation method has simple process, strong controllability, high production efficiency and is suitable for large-scale industrial production.

[0041] In some embodiments of the present application, in step S01, mixing polyphenylene phthalate, a binder and a plasticizer comprises:

[0042] Disperse a binder and a plasticizer in a polyphenylene phthalate solution (including polyphenylene phthalate and a solvent), stir, and obtain a functional layer slurry in the form of a suspended emulsion. In some specific embodiments, first disperse the binder in the polyphenylene phthalate solution, perform a first stirring, then add the plasticizer, perform a second stirring, and obtain a functional layer slurry. In the embodiment of the present application, the stirring rate, stirring time and stirring method of the first stirring and the second stirring are not specifically limited, and a suspended emulsion is obtained. For example, the stirring rate of the first stirring can be 600rpm-1000rpm, and the stirring time can be 1h; the stirring rate of the second stirring can be 400rpm-600rpm, and the stirring time can be 20min-50min. The above stirring method can be, but is not limited to, a mechanical stirring method, etc. Of course, the above stirring can also be replaced by an ultrasonic dispersion method, a high-pressure dispersion method, a medium dispersion method, a high-speed shear emulsification method, etc.

[0043] In the embodiment of the present application, the solvent in the polyphenylene phthalate solution includes but is not limited to one or more of dimethyl carbonate, dimethylacetamide and N-methylpyrrolidone.

[0044] In some embodiments of the present application, the binder is granular. The granular binder hardly undergoes morphological changes during the entire process of the battery separator. In order to reduce the agglomeration of the granular binder, improve the uniformity of the functional layer, and optimize its bonding performance, in some embodiments of the present application, the primary particle size of the granular binder is controlled within the range of 50nm-200nm. The particle size of the granular binder can be tested using a laser particle size analyzer.

[0045] In some embodiments of the present application, in step S02, the specific coating process is not limited, and technicians in the field can choose any coating process, such as micro-concave roller coating, doctor blade coating, narrow-slit extrusion coating, etc.

[0046] In some embodiments of the present application, in step S02, causing the cast film layer to undergo phase transformation includes:

[0047] passing the prefabricated membrane through a first coagulation bath and a second coagulation bath in sequence;

[0048] The first coagulation bath includes 30%-50% by mass of the first solvent, 0.5%-1% by mass of the first surfactant, and water; the second coagulation bath includes 10%-20% by mass of the second solvent, 0.1%-0.3% by mass of the second surfactant, and water. The appropriate coagulation bath concentration (the first and second solvent concentrations and the first and second surfactant concentrations) can improve the pore-forming quality of the functional layer, specifically, it is conducive to inducing the formation of the aforementioned three-dimensional network structure with appropriate porosity and pore size, controlling the permeability increment of the battery separator within a smaller range (for example, <50s / 100mL), and can effectively reduce the self-discharge and short circuit rate in the battery manufacturing process caused by the excessive pore size, and further optimize the battery yield and the final performance of the battery.

[0049] Specifically, the mass percentage of the first solvent in the first coagulation bath may be, but is not limited to, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, etc. The mass percentage of the second solvent in the second coagulation bath may be, but is not limited to, 10%, 12%, 15%, 18%, 20%, etc.

[0050] In some embodiments of the present application, the first solvent and the second solvent are independently selected from one or more of dimethyl carbonate (DMC), dimethylacetamide (DMA) and N-methylpyrrolidone (NMP). The first solvent and the second solvent may be the same or different. In some specific embodiments, the first solvent and the second solvent are the same and are selected from the same reagent as the solvent in the functional layer slurry.

[0051] Specifically, the mass percentage of the first surfactant in the first coagulation bath may be, but is not limited to, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, etc. The mass percentage of the second surfactant in the second coagulation bath may be, but is not limited to, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, etc. In some embodiments of the present application, the first surfactant and the second surfactant are independently selected from one or more of stearic acid, sodium dodecylbenzene sulfonate, and quaternary ammonium compounds. The first surfactant and the second surfactant may be the same or different.

[0052] In order to remove impurities such as residual solvents in the material, in some embodiments of the present application, in step S02, after passing through the second coagulation bath, the material passing through the second coagulation bath is also washed and dried. Specifically, clean water can be used for washing, for example, the material is passed through a tank filled with clean water, specifically, it can be passed through three clean water tanks in sequence. The above-mentioned drying can be oven drying, specifically, it can be dried at 60°C-90°C for 100s-300s.

[0053] The present application also provides a battery, including a positive electrode, a negative electrode and the battery separator provided in the present application, wherein the battery separator is located between the positive electrode and the negative electrode. Due to the use of the battery separator provided in the present application, the battery can achieve higher safety performance and better cycle performance.

[0054] In the embodiments of the present application, there is no limitation on the specific type of battery. For example, the battery may be an alkali metal ion battery such as a lithium ion battery and a sodium ion battery.

[0055] In some embodiments of the present application, the battery is a laminated battery, for example, a soft-pack laminated battery.

[0056] In the embodiments of the present application, the positive electrode may be any positive electrode known to those skilled in the art; the negative electrode may be any negative electrode known to those skilled in the art.

[0057] The embodiment of the present application also provides an electric device, including the battery provided in the embodiment of the present application. Since the battery provided in the embodiment of the present application is used to power the electric device, the electric device has strong market competitiveness.

[0058] In some implementations of the present application, the above-mentioned electrical equipment includes but is not limited to vehicles, 3C electronic products, etc. Among them, vehicles include but are not limited to new energy vehicles, electric vehicles, etc.

[0059] The technical solution of the present application is further illustrated by multiple embodiments below.

[0060] Example 1

[0061] (1) Add a certain amount of binder (specifically, polyvinylidene fluoride with a primary particle size of 50nm-200nm) to a poly(p-phenylene terephthalamide) solution (the solid content of poly(p-phenylene terephthalamide) is 15wt%, and the solvent is DMC), and stir for 1h using a mechanical stirrer at a speed of 900r / min. Then slowly add a certain amount of plasticizer (specifically triethyl phosphate), stir at a speed of 500r / min, and stir for 30min to obtain a functional layer slurry. In the functional layer slurry, the mass ratio of poly(p-phenylene terephthalamide), binder and plasticizer is 18:1:0.5.

[0062] A polyethylene base film with a porosity of 40%, a thickness of 12 μm, an air permeability of 180 s / 100 mL, a puncture strength of 0.45 kgf, a film breaking temperature of 130°C, and a width of 510 mm was selected, and the functional layer slurry was coated on the opposite sides of the base film using a micro-concave roller to obtain a prefabricated membrane.

[0063] The prefabricated membrane was sequentially passed through the first coagulation bath (40wt% DMC and 1wt% surfactant (specifically stearic acid), and the rest was water) and the second coagulation bath (10wt% DMC and 0.5wt% surfactant (specifically stearic acid), and the rest was water), washed with water in a cleaning tank, and dried at 80°C for 250s to obtain a battery separator with a functional layer thickness of 3μm.

[0064] Example 2

[0065] The difference from Example 1 is that in the functional layer slurry, the mass ratio of poly(p-phenylene terephthalamide), binder and plasticizer is 12:1:0.5.

[0066] Example 3

[0067] The difference from Example 1 is that in the functional layer slurry, the mass ratio of poly(p-phenylene terephthalamide), binder and plasticizer is 14:1:0.5.

[0068] Example 4

[0069] The difference from Example 1 is that in the functional layer slurry, the mass ratio of poly(p-phenylene terephthalamide), binder and plasticizer is 5:1:0.5.

[0070] Example 5

[0071] The difference from Example 1 is that in the functional layer slurry, the mass ratio of poly(p-phenylene terephthalamide), binder and plasticizer is 14:1:0.8.

[0072] Example 6

[0073] The difference from Example 1 is that: (1) in the functional layer slurry, the mass ratio of poly(p-phenylene terephthalamide), binder and plasticizer is 14:1:0.5;

[0074] (2) The formula of the first coagulation bath is: 30 wt% DMC and 1 wt% surfactant, and the balance is water; the formula of the second coagulation bath is: 15 wt% DMC and 0.5 wt% surfactant, and the balance is water.

[0075] Example 7

[0076] The difference from Example 1 is that: (1) in the functional layer slurry, the mass ratio of poly(p-phenylene terephthalamide), binder and plasticizer is 14:1:0.5;

[0077] (2) The formula of the first coagulation bath is: 50wt% DMC and 1wt% surfactant, and the balance is water; the formula of the second coagulation bath is: 10wt% DMC and 0.5wt% surfactant, and the balance is water.

[0078] In order to highlight the beneficial effects of the embodiments of the present application, the following comparative examples are provided.

[0079] Comparative Example 1

[0080] Prepare a poly(p-phenylene terephthalamide) solution (the solid content of poly(p-phenylene terephthalamide) is 15wt% and the solvent is DMC); select a polyethylene base film with a porosity of 40%, a thickness of 12μm, an air permeability of 180s / 100mL, a puncture strength of 0.45kgf, a film breaking temperature of 130°C, and a width of 510mm, and use a micro-concave roller to coat the poly(p-phenylene terephthalamide) solution on the opposite sides of the base film to obtain a prefabricated film.

[0081] The prefabricated membrane was sequentially passed through the first coagulation bath (40wt% DMC and 1wt% stearic acid, and the rest was water) and the second coagulation bath (10wt% DMC and 0.5wt% stearic acid, and the rest was water), washed in a cleaning tank, and dried at 80°C for 250s to obtain a battery separator.

[0082] Performance Testing

[0083] (1) Morphology observation: The battery separators of each embodiment and comparative example were placed in a -20°C dew point environment for 103 hours to observe whether there were curling or sagging. The results are summarized in Table 1. The photographs of the battery separators of Example 3, Example 5, and Comparative Example 1 after being placed in a -20°C dew point environment for 103 hours are shown in Table 1. Figure 2A , Figure 2B and Figure 4 shown.

[0084] The morphology of the surface of the functional layer away from the base film was observed under a scanning electron microscope (SEM). The SEM photo of Example 3 is as follows: Figure 3 shown.

[0085] (2) Membrane rupture temperature test: The membrane rupture temperature of each battery separator was tested using a thermomechanical analyzer (TMA). Specifically, the gas flow rate in the TMA was 100 mL / min, the tension was 0.03 N, the heating rate was 5 °C / min, and the termination temperature was 400 °C. The results are summarized in Table 1.

[0086] (3) Thermal shrinkage performance test: The battery separator (5 cm × 5 cm) was isothermally heat treated in a constant temperature oven at 130°C for 1 h. The thermal shrinkage of the battery separator in the transverse direction (TD) and the longitudinal direction (MD) was calculated. The formula for calculating thermal shrinkage is: Single-side thermal shrinkage rate = (original length of single side - length after heat treatment) / original length of single side × 100%. The results are summarized in Table 1.

[0087] (4) Air permeability test: The air permeability of the battery separator C1 and the base film C2 is tested using an air permeability tester. Specifically, the battery separator is laid flat on the measuring position of the air permeability tester to test its air permeability value; 10 points along the TD direction of each battery separator are selected for testing and the average value is taken.

[0088] (5) High temperature cycle performance test of batteries

[0089] ① Preparation of positive electrode and test of compaction density: The positive electrode active material (lithium iron phosphate), binder (specifically PVDF) and conductive agent (specifically conductive carbon black) of each embodiment and comparative example were mixed in a mass ratio of 90:5:5, dispersed in a solvent (specifically N-methylpyrrolidone), and mixed evenly to obtain a positive electrode slurry;

[0090] The positive electrode slurry is coated on the opposite sides of the positive electrode current collector (specifically, carbon-coated aluminum foil), and the positive electrode is obtained after drying and rolling.

[0091] Preparation of negative electrode: The negative electrode active material (graphite), binder (specifically PVDF) and conductive agent (specifically conductive carbon black) of each embodiment and comparative example are mixed in a mass ratio of 90:5:5, dispersed in a solvent (specifically N-methylpyrrolidone), and mixed evenly to obtain a negative electrode slurry;

[0092] The negative electrode slurry is coated on the opposite sides of the negative electrode current collector (specifically copper foil), and the negative electrode is obtained after drying and rolling.

[0093] ② Preparation of test cells: In a glove box, the above-mentioned positive electrode, each battery separator and negative electrode are assembled into a laminated battery, and each test cell is obtained after injecting the electrolyte. The electrolyte is an organic solvent containing a lithium salt (specifically lithium hexafluorophosphate), wherein the lithium salt concentration is 1 mol / L, and the organic solvent includes ethylene carbonate, ethyl methyl carbonate, dimethyl carbonate and vinylene carbonate, wherein the mass ratio of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate is 3:6:1, and the mass fraction of vinylene carbonate is 1%.

[0094] ③Electrochemical performance test: Connect each test battery prepared in step ③ above to a battery cabinet, charge to 3.8V at 1C constant current at 45°C, charge to a current ≤0.02C at constant voltage, let stand for 30 minutes, and then discharge to 2.5V at 1C constant current. The above is one cycle, and the battery capacity retention rate after 500 cycles is recorded. The cycle retention rate after 500 cycles = discharge capacity of the 500th cycle / first discharge capacity × 100%. The results are summarized in Table 1.

[0095] (6) Peel strength test:

[0096] The battery separators prepared in the above-mentioned embodiments and comparative examples are respectively hot-pressed on the surfaces of the opposite sides of the positive electrode prepared according to the above-mentioned process, and then a high-temperature glue layer is provided on the surface of the functional layer of the battery separator on one side (referred to as the first battery separator) facing away from the positive electrode, and the battery separator on the other side (referred to as the second battery separator) is separated from the positive electrode by 5 mm along its length direction and fixed on the upper side of the tensile machine, and one side of the second battery separator is fixed to the lower side of the tensile machine by high-temperature glue, and the sample is fixed in the middle of the fixture;

[0097] Set the moving rate of the tensile testing machine to 100 mm / min and the travel distance to 50 mm. After straightening the diaphragm, reset it to zero and start the test according to the above parameter settings. After the test, record the average tensile force (N) of the test results. According to the formula: peel strength = average tensile force (N) / test sample width (m), the results are summarized in Table 1.

[0098] Table 1

[0099]

[0100] From the data in Table 1, it can be seen that the battery separator provided in the embodiment of the present application has a higher film breaking temperature and exhibits a lower high-temperature shrinkage rate, indicating that it has good high-temperature resistance and also has better air permeability; in particular, the battery separator provided in the embodiment of the present application has high peel strength with the positive electrode and does not curl or droop under the assembly conditions of the battery, thereby further improving the high-temperature cycle performance of the final battery. In addition, by comparing the data of Example 1 and Example 4, it can be found that when the mass ratio of the polyphenylene phthalate, binder and plasticizer of the functional layer is controlled within the range further suggested in the present application (Example 1), the comprehensive performance of the battery separator is better and more conducive to improving the high-temperature cycle performance of the battery.

[0101] The above is an exemplary embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made thereto without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A battery separator, characterized in that: The invention comprises a base film and a functional layer arranged on at least one surface of the base film, wherein the functional layer comprises polyphenylene phthalamide, a binder and a plasticizer.

2. The battery separator according to claim 1, characterized in that: The mass ratio of the plasticizer to the polyphenylene phthalate is 1:(8-300).

3. The battery separator according to claim 1 or 2, characterized in that: The mass ratio of the polyphenylene phthalate, the binder and the plasticizer satisfies (8-30):1:(0.1-1).

4. The battery separator according to claim 3, characterized in that: The mass ratio of the polyphenylene phthalate, the binder and the plasticizer satisfies (12-18):1:(0.3-0.5).

5. The battery separator according to any one of claims 1 to 4, characterized in that: The plasticizer includes one or more of triethyl phosphate, tributyl phosphate, tricresyl phosphate, dioctyl adipate, diisodecyl adipate, dioctyl azelate, dioctyl sebacate, dioctyl phthalate, dibutyl phthalate, dimethyl phthalate, diethyl phthalate, epoxy fatty acid butyl ester, dipentaerythritol ester and ethylene glycol ester; and / or The binder includes one or more of polyvinylidene fluoride, polymethyl methacrylate, polyamide and polyacrylic acid.

6. The battery separator according to any one of claims 1 to 5, characterized in that: The functional layer has a three-dimensional network structure formed by overlapping fibers, and the granular binder is dispersed in the three-dimensional network structure; and / or The material of the fiber includes the polyphenylene phthalate and the plasticizer; and / or The particle size of the granular binder is 50nm-200nm.

7. The battery separator according to any one of claims 1 to 6, characterized in that: The porosity of the base film is 30%-55%; and / or the material of the base film is selected from one or more of polyolefin, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyimide, polyester and polyurethane.

8. The battery separator according to any one of claims 1 to 7, characterized in that: The functional layers are disposed on two opposite surfaces of the base film.

9. The battery separator according to any one of claims 1 to 8, characterized in that: The liquid absorption rate increment of the battery separator relative to the base film is 50%-100%.

10. The battery separator according to any one of claims 1 to 9, characterized in that: The air permeability increment of the battery separator relative to the base film is ≤50s / 100mL.

11. The battery separator according to any one of claims 1 to 10, characterized in that: The puncture strength increment of the battery separator relative to the base film is 0.5kgf-2kgf.

12. The battery separator according to any one of claims 1 to 11, characterized in that: The transverse shrinkage rate of the battery separator at 130° C. is ≤3.5%, and the longitudinal shrinkage rate of the battery separator at 130° C. is ≤4.5%.

13. The battery separator according to any one of claims 1 to 12, characterized in that: The thickness of the functional layer is 1 μm-4 μm.

14. A method for preparing a battery separator according to any one of claims 1 to 13, characterized in that: include: Mixing the polyphenylene phthalamide, the binder and the plasticizer to obtain a functional layer slurry; The functional layer slurry is coated on at least one side of the base film to obtain a prefabricated film with a cast film layer, and the cast film layer is phase-converted to form the functional layer to obtain the battery separator.

15. The method for preparing a battery separator according to claim 14, characterized in that: The step of causing the cast film layer to undergo phase transformation comprises: Passing the prefabricated membrane through a first coagulation bath and a second coagulation bath in sequence; The first coagulation bath comprises 30%-50% by mass of a first solvent, 0.5%-1% by mass of a first surfactant, and water; the second coagulation bath comprises 10%-20% by mass of a second solvent, 0.1%-0.3% by mass of a second surfactant, and water; The first solvent and the second solvent are independently selected from one or more of dimethyl carbonate, dimethylacetamide and N-methylpyrrolidone; The first surfactant and the second surfactant are independently selected from one or more of stearic acid, sodium dodecylbenzene sulfonate and quaternary ammonium compounds.

16. A battery, characterized in that: The invention comprises a positive electrode, a negative electrode and a battery separator according to any one of claims 1 to 13, wherein the battery separator is located between the positive electrode and the negative electrode.

17. An electrical equipment, characterized in that: Comprising the battery of claim 16.